Phylogenetic and Taxonomic Analyses of Five New Wood-Inhabiting Fungi of Botryobasidium, Coltricia and Coltriciella (Basidiomycota) from China - Qian Zhou; Qianquan Jiang; Xin Yang; Jiawei Yang; Changlin Zhao; Jian Zhao (Journal of Fungi, 2024)
In this present study, five new wood-inhabiting fungal taxa, Botryobasidium gossypirubiginosum, Botryobasidium incanum, Botryobasidium yunnanense, Coltricia zixishanensis, and Coltriciella yunnanensis are proposed. Botryobasidium gossypirubiginosum is distinguished by its slightly rubiginous hymenial surface, monomitic hyphal system, which branches at right angles, and subglobose, smooth basidiospores (14–17.5 × 13–15.5 µm); B. incanum is characterized by its white to incanus basidiomata having a hypochnoid hymenial surface, and ellipsoid, smooth basidiospores (6.5–8.5 × 3.5–5 µm); B. yunnanense is characterized by its buff to slightly yellowish hymenial surface, monomitic hyphal system, and broadly ellipsoid to globose, smooth, thick-walled basidiospores (11.5–14.5 × 9.5–10.5 µm); Coltricia zixishanensis differs in its rust brown pileal surface, and ellipsoid, thick-walled basidiospores (5–6.5 × 4–4.5 µm). Coltriciella yunnanensis is distinguished by its tiny pilei, short stipe, and navicular, verrucose basidiospores (10.5–12.5 × 6–7 µm). Sequences of ITS and nLSU genes were used for phylogenetic analyses using the maximum likelihood, maximum parsimony, and Bayesian inference methods. The phylogenetic results inferred from ITS sequences revealed that B. gossypirubiginosum was closely related to B. robustius; the species B. incanum was grouped with B. vagum; B. yunnanense was related to B. indicum. The species C. zixishanensis was grouped with C. confluens and C. perennis. ITS sequences revealed that C. zixishanensis was grouped into the genus Coltriciella, in which it was grouped with Co. globosa and Co. pseudodependens.